2001
DOI: 10.1073/pnas.231324698
|View full text |Cite
|
Sign up to set email alerts
|

A new class of oxidosqualene cyclases directs synthesis of antimicrobial phytoprotectants in monocots

Abstract: Here we show the novel oxidosqualene cyclase AsbAS1 catalyzes the first committed step in the synthesis of antifungal triterpenoid saponins that accumulate in oat roots. We also demonstrate that two sodium azide-generated saponin-deficient mutants of oat, which define the Sad1 genetic complementation group, are defective in the gene encoding this enzyme and provide molecular genetic evidence indicating a direct link between AsbAS1, triterpenoid saponin biosynthesis, and disease resistance. Orthologs of AsbAS1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
204
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(210 citation statements)
references
References 45 publications
4
204
0
2
Order By: Relevance
“…Previously, we have shown that Sad1 and Sad2 are expressed specifically in the root tip cells (Haralampidis et al, 2001;Qi et al, 2006). RNA gel blot analysis indicated that expression of SCPL1 was also root specific ( Figure 2B).…”
Section: Scpl1 Is Synonymous With Sad7mentioning
confidence: 56%
See 3 more Smart Citations
“…Previously, we have shown that Sad1 and Sad2 are expressed specifically in the root tip cells (Haralampidis et al, 2001;Qi et al, 2006). RNA gel blot analysis indicated that expression of SCPL1 was also root specific ( Figure 2B).…”
Section: Scpl1 Is Synonymous With Sad7mentioning
confidence: 56%
“…The synthesis of avenacins is tightly regulated and is restricted to the epidermal cells of the root tip (Haralampidis et al, 2001). Previously, we have shown that Sad1 and Sad2 are expressed specifically in the root tip cells (Haralampidis et al, 2001;Qi et al, 2006).…”
Section: Scpl1 Is Synonymous With Sad7mentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike operons, the genes within these clusters are transcribed separately. The five plant clusters are for the synthesis of cyclic hydroxamic acids in maize (Frey et al, 1997(Frey et al, , 2003(Frey et al, , 2009von Rad et al, 2001;Jonczyk et al, 2008), triterpenes in oat (Avena sativa) and Arabidopsis (the avenacin and thalianol clusters, respectively; Papadopoulou et al, 1999;Haralampidis et al, 2001;Qi et al, 2004Qi et al, , 2006Field and Osbourn, 2008;Mylona et al, 2008;Mugford et al, 2009), and diterpenes in rice (Oryza sativa; the momilactone and phytocassane clusters; Sakamoto et al, 2004;Wilderman et al, 2004;Shimura et al, 2007;Swaminathan et al, 2009). These clusters are diverse in organization and function and all appear to have evolved independently (Field and Osbourn, 2008;Frey et al, 2009;Osbourn and Field, 2009;Swaminathan et al, 2009).…”
Section: Operon-like Gene Clusters In Plantsmentioning
confidence: 99%